Smoking, depression, and hospital costs of respiratory cancers: Examining race and sex variation. Issue 1 (1st May 2017) - Husaini, Baqar A.; Levine, Robert S.; Lammers, Phillip; Hull, Pam; Novotny, Meggan; Moonis, Majaz
Abstract : Objective: To investigate the effect of smoking and depression on hospital costs for lung cancer (LC). Methods: We extracted data on depression, smoking history, demographics, and hospital charges for patients with respiratory cancers (ICD-9 codes 161–163, 165) from the 2008 Tennessee Hospital Discharge Data System. The sample ( n =6665) was mostly white (86%) and male (57%). Age-adjusted rates were developed in accordance with Centers for Disease Control and Prevention methods, and hospital costs were compared for patients with LC with versus without depression and a smoking history. Results: Three findings ( P <0.001) emerged: (1) the LC rate was higher among blacks than among whites, and higher among men than among women; (2) while 66% of LC patients smoked (more men than women without racial variation), 24% had depression (more females and whites were depressed); (3) the LC hospital cost was 54% higher than the non-LC hospital cost, and this cost doubled for patients with LC with depression and smoking versus those without such characteristics. Conclusion: While LC is more prevalent among blacks and men, depression is higher among female and white patients. Since depression with higher costs existed among LC patients, our findings point to (1) the possibility of cost savings by diagnosing and treating depression among LC patients, and (2) implementation of proven smoking cessation programs to reduce LC morbidity and hospital costs.